Clinical and molecular characterization of a large family with an interstitial 15q11q13 duplication - Piard, Juliette; Philippe, Christophe; Marvier, Marie; Beneteau, Claire; Roth, Virginie; Valduga, Mylène; Béri, Mylène; Bonnet, Céline; Grégoire, Marie-José; Jonveaux, Philippe; Leheup, Bruno (American journal of medical genetics. Part A, 2010)
The clinical significance of an interstitial duplication of chromosome 15q11q13 is still not well documented. This abnormality has been associated with autistic spectrum disorders (ASD) and varying degrees of mental retardation. The clinical variability appears to be influenced by the parental origin of the duplication. We present here the clinical evaluation and psychological assessment of the largest reported family with 12 carriers on three generations. Patients exhibit mental retardation, motor and visuo‐motor skills impairments and adaptive functioning deficit without formal diagnosis of autism. There appeared to be evidence in the family of reduced penetrance in duplication of paternal origin. This familial 15q11q13 duplication was precisely investigated by cytogenetic and molecular techniques including fluorescence in situ hybridization (FISH), PCR analysis of microsatellite markers, array‐comparative genomic hybridization analysis (Array‐CGH) and semi‐quantitative methylation‐sensitive PCR. Results showed an inherited 15q11q13 duplication of maternal origin in 10 patients and of paternal origin in the remaining two. The size of the duplicated area was around 6 Mb with breakpoints in accordance with those previously reported. This report extends the clinical spectrum of the 15q11q13 duplication, and we recommend the investigation of 15q11q13 duplication not only in subjects with autistic spectrum disorder but also in patients with low normal intelligence and dyspraxia. © 2010 Wiley‐Liss, Inc.